Synchronous random switching frequency modulation technique based on the carrier phase shift to reduce the PWM noise. Issue 4 (3rd January 2020) - Zhang, Wentao; Xu, Yongxiang; Ren, Jingwei; Su, Jianyong; Zou, Jibin
Abstract : Pulse width modulation (PWM) technique brings harsh acoustic noise in motor drive system. Thus, synchronous random switching frequency modulation (SRSFM) technique based on carrier phase shift for paralleled three‐phase voltage source inverters is proposed in this study to eliminate the PWM noise. The proposed SRSFM technique is able to remove the high‐frequency PWM noise more effectively than the conventional random switching frequency PWM; it not only completely eliminates the PWM noise nearby odd‐order carrier frequency but also reduces PWM vibration noise around even‐order carrier frequency depending on the switching frequency variation range. Furthermore, the SRSFM technique is simple to implement and requires no additional hardware. Finally, the effectiveness of the proposed method is verified by detailed experimental results.